The Effect Of Project-Based Learning On The Students’ Speaking Ability - Firdayanti Firdaus; Adryan Septiady (Journal on Education, 2023)
This research investigated the effect of Project-based learning on students’ speaking ability. This was a mix research, qualitative and quantitative. Qualitative was used to describe the implementation of the project based learning in Accounting Study Program students. The quantitative research used was a pre-experimental research with a One Group Pretest-Posttest design to find the effect of project based learning on the students’ speaking ability. There was a single sample, 35 students, of the population (1st to 4th semester Accounting Study Program Students of Universitas Potensi Utama). The qualitative data were collected by using interview, observation, and documentation. The quantitative data were collected by using tests, pre-test and post-test. Since this study was intended to find the effect of the Project-Based Learning toward students’ speaking ability, the quantitative data were analyzed statistically by paired sample t-test by using IBM SPSS 22 for Windows. The result of analysis showed that there was a significant effect of Project-Based Learning on the students’ speaking ability. It was an effective method in teaching speaking because it improves students’ speaking ability, build students’ team work skills, increase students’ problem solving skill, and stimulates students to be active, communicative, creative, and innovative. Therefore, it is strongly recommended to be applied in the teaching speaking.